Entrapment of a volatile lipophilic aroma compound (D-limonene) in spray dried water-washed oil bodies naturally derived from sunﬂower seeds (Helianthus annus) - Fisk, Ian D.; Linforth, Rob S.T.; Trophardy, Gil; Gray, David A. (Elsevier, 2013)
Oil bodies are natural emulsions that can be extracted from oil seeds and have previously been shown to be stable after spray drying. The aim of the study was to evaluate for the ﬁrst time if spray dried water-washed oil bodies are an effective carrier for volatile lipophilic actives (theﬂavour compound D-limonene was used as an example aroma compound). Water-washed oil bodies were blended with maltodextrin and D-limonene and spray dried using a Buchi B-191 laboratory spray dryer. Lipid and D-limonene retention was 89–93% and 24–27%. Samples were compared to processed emulsions containing sunﬂower oil and D-limonene and stabilised by either lecithin or Capsul. Lecithin and Capsul processed emulsions had a lipid and D-limonene retention of 82–89%, 7.7–9.1% and 48–50%, 55–59% respectively indicating that water-washed oil bodies could retain the most lipids and Capsul could retain the most D-limonene. This indicates that whilst additional emulsiﬁers may be required for future applications of water-washed oil bodies as carriers of lipophilic actives, oil bodies are excellent agents for lipid encapsulation.